Normalizing object classes in fuzzy object-oriented database schema - Ban, Đoàn Văn; Hà, Hồ Cẩm; Quảng, Vũ Đức (Journal of Computer Science and Cybernetics, 2012)
<span lang="VI" style="font-family: "Times New Roman","serif"; font-size: 11pt; mso-ansi-language: VI; mso-fareast-font-family: "Times New Roman"; mso-fareast-language: VI; mso-bidi-language: AR-SA; mso-bidi-font-size: 12.0pt;">In this article, we focus on reseaching fuzzy dependencies between attributes in an object class. Similarly in the fuzzy (clear) relational database, we propose the fuzzy object normal forms (1FONF, 2FONF, 3FONF) and the algorithms normalizing classes into norm forms in fuzzy object-oriented databases.